Removal of Textile dye by Using Activated Carbon in Aqueous Solution - Insuwan, Wilaiporn; Moonchaisook, Khattiya; Junkrin, Benjamaporn (Naresuan University Journal: Science and Technology (NUJST), 2020)
Two textile dye (indigo carmine and acid blue 25) were removed using activated carbon (AC) as solid adsorbent. Effects of various parameters such as adsorbent dosage, contact time, kinetics and thermodynamic properties were investigated by batch adsorption technique. The results shown that the adsorption kinetics of textile dye was determined by the pseudo-second order model and adsorption isotherms fitted very well with Langmuir model. In addition, thermodynamic properties indicated that the adsorption of both textile dye on AC were endothermic and spontaneous process. The maximum adsorption capacities (qm) of indigo carmine and acid blue 25 onto AC was 89.29-104.17 mg/g and 1,428.00-2,000.00 mg/g, respectively. This results could be explained by stronger interaction between acid blue 25 and AC. This work indicated that AC can be used as an alternative adsorbent for removal of textile dye especially acid blue 25, due to the low cost and high efficiency of adsorption capacity. Keywords: textile dye, adsorption, kinetics, activated carbon